CONTRIBUTION TO THE KNOWLEDGE OF THE SPIDER FAUNA (ARACHNIDA, ARANEAE) ON THE FRUŠKA GORA MT. (Acta Entomologica Serbica, 2010)
Fruška Gora Mountain. In this paper 93 species represent new findings for the investigated area, while 17 of them such as Eresus moravicus Rezač, 2008 , Steatoda paykulliana (Walckenaer, 1805), Heterotheridion nigrovariegatum Simon, 1873, Donacochara speciosa (Thorell 1875), Neottiura suaveolens (Simon, 1879), Saloca diceros (O.P.-Cambridge, 1871), Minicia marginella (Wider, 1834), Tetragnatha striata L. Koch 1862, Larinioides suspicax (O.P.-Cambridge 1876), Dictyna civica (Linnaeus, 1758), Clubiona pseudoneglecta Wunderlich, 1994, Gnaphosa opaca Herman 1879, Philodromus marmoratus Kulczynski 1891, Ozyptila scabricula (Westring 1851), Leptorchestes berolinensis (C.L. Koch, 1846), Pseudeuophrys obsoleta (Simon, 1868) and Synageles hilarulus (C.L. Koch, 1851) represent new records for the Serbian spiders fauna. In the manuscript, some new and previous interesting findings are discussed, and some revision of literature data is done.